Çatalhöyük: the leopard changes its spots. A summary of recent work. (4th July 2014) - Hodder, Ian
Abstract: This paper summarises and interprets data from the Neolithic site ot Çatalhöyük East collected between 2000 and 2008, while at the same time integrating data from earlier and more recent excavation seasons. The paper focuses on evidence for change during the occupation of the site, arguing for an increase in the size and density of occupation into the middle levels associated with symbolic and ritual elaboration within an aggressively egalitarian community. The middle 'classic' levels at Çatalhöyük were associated with increased workload, physical stresses and illness. The pressures were relieved in the upper levels after 6500 BC by shifts to greater mobility, increased economic independence of houses and dispersal of population. This shift in the upper levels may be of relevance to the spread of farming populations into northwestern Anatolia and Europe. Özet: Bu makalede, 2000-2008 yılları arasında Çatalhöyük Neolitik yerleşiminin doğusundan elde edilen veriler özetlenmekte ve yorumlanmakta, aynı zamanda daha önceki ve son yıllardaki kazılardan elde edilen veriler birleştirilerek değerlendirilmektedir. Makalede son derece eşitlikçi bir toplum içinde sembolik ve törensel ayrıntılar ile ilişkili olarak orta tabakalara kadar yerleşimin büyüklüğü ve yoğunluğunda bir artış olduğu ileri sürülerek, Çatalhöyük'ün yerleşim gördüğü süre boyunca ortaya çıkan değişiklikler üzerinde durulmaktadır. Çatalhöyük'te orta 'klasik' tabakalar artan iş yükü, fiziksel baskılar ve hastalıkla ilişkilendirilmiştir. M.Ö. 6500'den sonra üst tabakalarda daha fazla hareketlilik, evlerin artan ekonomik bağımsızlığı ve nüfusun yayılması ile bu baskılar biraz rahatlamıştır. Üst tabakalardaki bu değişim, Kuzeybatı Anadolu'ya ve Avrupa'ya çiftçi nüfusun yayılmasında önemli rol oynamış olabilir.